Reactions of 4-Pyrones with Azomethine Ylides as a Chemoselective Method for the Construction of Multisubstituted Pyrano[2,3-c]pyrrolidines - Obydennov, Dmitrii L.; Steben’kov, Vyacheslav D.; Obydennov, Konstantin L.; Usachev, Sergey A.; Moshkin, Vladimir S.; Sosnovskikh, Vyacheslav Y. (Synthesis, 2021)
4-Pyrones bearing electron-donating and electron-withdrawing groups react with nonstabilized azomethine ylides to form pyrano[2,3-c]pyrrolidines in moderate to good yields. The reaction proceeds chemoselectively as a 1,3-dipolar cycloaddition of the azomethine ylide at the carbon–carbon double bond of the pyrone activated by the electron-withdrawing substituent. The reactivity of 4-pyrones toward azomethine ylides was rationalized by computational studies with the use of reactivity indexes. The pyrano[2,3-c]pyrrolidine moiety could be modified, for example by a ring-opening transformation under the action of hydrazine to provide pyrazolyl-substituted pyrrolidines.
Keywords: 4-pyrones; azomethine ylides; cycloaddition; pyrano[2,3-c]pyrrolidine; chemoselectivity